2007
DOI: 10.1186/1471-2458-7-63
|View full text |Cite
|
Sign up to set email alerts
|

Gender distribution of adult patients on highly active antiretroviral therapy (HAART) in Southern Africa: a systematic review

Abstract: Background: HIV and AIDS are significant and growing public health concerns in southern Africa. The majority of countries in the region have national adult HIV prevalence estimates exceeding 10 percent. The increasing availability of highly active antiretroviral therapy (HAART) has potential to mitigate the situation. There is however concern that women may experience more barriers in accessing treatment programs than men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
112
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(132 citation statements)
references
References 34 publications
19
112
0
1
Order By: Relevance
“…Such barriers include (but are not limited to) transport costs and time, loss of earnings, lack of financial resources, stigma, lack of family support and perceived need when individuals are asymptomatic. [16][17][18][19][20][21][22] Future research must look for ways to overcome these barriers, either directly or through other interventions, to improve post-VCT medical care. ■…”
Section: Discussionmentioning
confidence: 99%
“…Such barriers include (but are not limited to) transport costs and time, loss of earnings, lack of financial resources, stigma, lack of family support and perceived need when individuals are asymptomatic. [16][17][18][19][20][21][22] Future research must look for ways to overcome these barriers, either directly or through other interventions, to improve post-VCT medical care. ■…”
Section: Discussionmentioning
confidence: 99%
“…Despite early concerns that women may be disadvantaged in ART programmes, disproportionately more women than men have accessed ART in Southern Africa. [2] In South Africa, for example, 60% of eligible women were receiving ART by mid-2011 compared with 41% of eligible men. [3] Men have a higher mortality than women when receiving ART.…”
mentioning
confidence: 99%
“…He reported that women who accessed HAART services were more than men by a ratio of 3: 1 and 20% of the women were more likely to adhere to HAART as compared to men. This could be explained that the large numbers of women were more familiar with the health care services as compared to men and especially women interacted with the clinics when accessing other services like antenatal, maternity and family planning as this was also supported by Muala and colleagues [19]. The authors further explained men were thought to be slower in uptake of HAART services due to the stigma acquired with it.…”
Section: Discussionmentioning
confidence: 52%